2003
DOI: 10.1046/j.1440-1746.2003.03063.x
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant hepatitis C virus infection and its effect on the post‐transplant course of living renal allograft recipients

Abstract: HCV infection does not seem to influence patient and graft survival within a medium-time follow up in living allograft recipients, and anti-HCV-antibody positive status (alone) is not a contraindication for renal transplantation. However, further studies are needed to better define the role of HCV infection in long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…However, HCV-infected renal allograft recipients with abnormal liver function had inferior survival rates. Several other studies [131,132,133,134,135], with the exception of one [136], with shorter than 10-year follow-up periods reported no adverse impact of HCV infection on graft and/or patient survival. The promising results of the aforementioned studies suggest that for many patients, the benefits of renal transplantation outweigh its potential risks imposed by immunosuppression.…”
Section: Natural History and Liver Histopathology In Hcv-infected Hd mentioning
confidence: 98%
“…However, HCV-infected renal allograft recipients with abnormal liver function had inferior survival rates. Several other studies [131,132,133,134,135], with the exception of one [136], with shorter than 10-year follow-up periods reported no adverse impact of HCV infection on graft and/or patient survival. The promising results of the aforementioned studies suggest that for many patients, the benefits of renal transplantation outweigh its potential risks imposed by immunosuppression.…”
Section: Natural History and Liver Histopathology In Hcv-infected Hd mentioning
confidence: 98%
“…3, 4). It was reported by Einollahi et al 29 that the 7-year patient survival rate was 89.9% in their HCV-positive group vs 95.5% in their HCVnegative group (P = 0.74), while the 7-year graft survivals were 82.0% and 75.0%, respectively (P = 0.39). They concluded that HCV infection did not seem to infl uence patient or graft survival within a medium-time follow up in living allograft recipients, and anti-HCV-antibody-positive status alone was not a contraindication for renal transplantation.…”
Section: Discussionmentioning
confidence: 82%
“…A multivariate analysis showed similar seven-year patient and graft survival rates in anti-HCV positive and anti-HCV negative RT recipients. 23 In another study, anti-HCV positive RT patients had a better five-year survival than anti-HCV negative patients. 24 In an earlier study we had found HCV infection to be a bad prognostic indicator for patient and graft survival duration in RT recipients and infections were the commonest cause of death in our patients.…”
Section: Discussionmentioning
confidence: 95%